Low-dose oncolytic adenovirus therapy overcomes tumor-induced immune suppression and sensitizes intracranial gliomas to anti-PD-1 therapy. Issue 2 (3rd February 2020) - Belcaid, Zineb; Berrevoets, Cor; Choi, John; van Beelen, Edward; Stavrakaki, Eftychia; Pierson, Tessa; Kloezeman, Jenneke; Routkevitch, Denis; van der Kaaij, Mariëlle; van der Ploeg, Alicia; Mathios, Dimitrios; Sleijfer, Stefan; et al.
Abstract: Background: The tumor-selective human adenovirus Delta24-RGD is currently under investigation in phase II clinical trials for patients with recurrent glioblastoma (GBM). To improve treatments for patients with GBM, we explored the potential of combining Delta24-RGD with antibodies targeting immune checkpoints. Methods: C57BL/6 mice were intracranially injected with GL261 cells and treated with a low dose of Delta24-RGD virus. The expression dynamics of ten co-signaling molecules known to affect immune activity were assessed in tumor infiltrating immune cells by flow cytometry after viral injection. The anti-tumor activity was measured by tumor cell killing and IFNγ production in co-cultures. Efficacy of the combination viro-immunotherapy was tested in vitro and in the GL261 and CT2A orthotopic mouse GBM models. Patient-derived GBM cell cultures were treated with Delta24-RGD to assess changes in PD-L1 expression induced by virus infection. Results: Delta24-RGD therapy increased intratumoral CD8 + T cells expressing ICOS and PD-1. Functionality assays confirmed a significant positive correlation between tumor cell lysis and IFNγ production in ex vivo cultures (Spearman r = 0.9524; p < 0.01). Co-cultures significantly increased IFNγ production upon treatment with PD-1 blocking antibodies. In vivo, combination therapy with low dose Delta24-RGD and anti-PD-1 antibodies significantly improved outcome compared to single agent therapy in both syngeneic mouse glioma models and increased PD-1 + tumor infiltrating CD8 + T cells. Delta24-RGD infection induced tumor-specific changes in PD-L1 expression in primary GBM cell cultures. Conclusions: This study demonstrates the potential of using low dose Delta24-RGD therapy to sensitize glioma for combination with anti-PD-1 antibody therapy.